"We're all in this together"? The search for collective belonging in a globalised single industry town. Issue 1 (14th March 2017) - Hurd, Fiona; Dyer, Suzette
Abstract : Purpose: Communities of work are a phenomenon closely associated with government social and industrial policy, and can be tracked in contemporary examples globally alongside industrial development. The purpose of this paper is to explore community identity within a town which was previously single industry, but has since experienced workforce reduction and to a large degree, industry withdrawal. Design/methodology/approach: Using an inductive approach, the researchers interviewed 32 participants who had resided (past or present) within the instrumental case study town. A thematic analytical framework, drawing on the work of Boje (2007) was employed. Findings: A significant theme to emerge from the participants was the public assertion of social cohesion and belonging. However, what was interesting, was that beneath this unified exterior, lay accounts of multiple forms of demarcation. Drawing on Benedict Anderson's (1983) notion of the imagined community, and Bauman's (2001) identity in globalisation, this contradiction is conceptualised as boundary-making moments of identification and disidentification. Research limitations/implications: This research is specific to the New Zealand context, although holds many points of interest for the wider international audience. The research provides a broad example of the layering of the collective and individual levels of identity. Social implications: This research provides a voice to the wider individual, community and societal implications of managerial practices entwined with political decisions. This research encourages managers and educators in our business schools to seek to understand the relationship between the political, corporate, community and individual realms. Originality/value: This research makes a significant contribution to understandings of the interconnectedness of social policy, industry, and the lived experiences of individuals. Moreover, it contributes to the broader single industry town literature, which previously has focussed on stories of decline from a North American context.